Bifidobacterium lactis combined with Lactobacillus plantarum inhibit glioma growth in mice through modulating PI3K/AKT pathway and gut microbiota - Wang, Li; Li, Sui; Fan, Huali; Han, Mingyu; Xie, Jie; Du, Junrong; Peng, Fu (Frontiers in Microbiology, 2022)
Glioma is a common primary aggressive tumor with limited clinical treatment. Recently, growing researches suggests that gut microbiota is involved in tumor progress, and several probiotics can inhibit tumor growth. However, evidence for the effect of probiotics on glioma is lacking. Here, we found that Bifidobacterium (B.) lactis combined with Lactobacillus (L.) plantarum reduced tumor volume, prolonged survival time and repaired the intestinal barrier damage in an orthotopic mouse model of glioma. Experiments demonstrated that B. lactis combined with L. plantarum suppressed the PI3K/AKT pathway and down-regulated the expression of Ki-67 and N-cadherin. The glioma-inhibitory effect of probiotic combination also related to the modulation of gut microbiota composition, which charactered by increasing relative abundance of Lactobacillus and decreases in some potential pathogenic bacteria. Additionally, probiotic combination altered fecal metabolites represented by fatty acyls and organic oxygen compounds. Together, our results prove that B. lactis combined with L. plantarum can inhibit glioma growth by suppressing PI3K/AKT pathway and regulating gut microbiota composition and metabolites in mice, thus suggesting the potential benefits of B. lactis and L. plantarum against glioma.